Connecting VLBI and Gaia Celestial Reference Frames - Malkin, Zinovy (Frontiers in Astronomy and Space Sciences, 2016)
The current state of the link problem between radio and optical celestial reference frames is considered. The main objectives of the investigations in this direction during the next few years are the preparation of a comparison and the mutual orientation and rotation between the optical Gaia Celestial Reference Frame (GCRF) and the 3rd generation radio International Celestial Reference Frame (ICRF3), obtained from VLBI observations. Both systems, ideally, should be a realization of the ICRS (International Celestial Reference System) at micro-arcsecond level accuracy. Therefore, the link accuracy between the ICRF and GCRF should be obtained with similar error level, which is not a trivial task due to relatively large systematic and random errors in source positions at different frequency bands. In this paper, a brief overview of recent work on the GCRF–ICRF link is presented. Additional possibilities to improve the GCRF–ICRF link accuracy are discussed. The suggestion is made to use astrometric radio sources with optical magnitude to 20m rather than to 18m as currently planned for the GCRF–ICRF link. In addition, the use of radio stars is also a prospective method to obtain independent and accurate orientation between the Gaia frame and the ICRF.